Impact of prenatal dental on maternal and children's health: a integrative review (Research, Society and Development, 2021)
This study aimed to evaluate dental care during prenatal care, focusing on its importance for maternal and child oral health. The literature review was carried out based on the PRISMA guidelines, where a bibliographic survey of studies published in the last 10 years was carried out, which were present in the databases of PubMed/Medline, Scopus, LILACS, SciELO and Cocrhane. The selected studies found that dental problems, especially periodontal diseases, are considered risk factors for the increase in cases of dental caries in early childhood, as well as cases of premature births and low birth weight. It is possible to conclude that dental monitoring during prenatal care is extremely important for the maintenance of maternal and child oral health, and that improvements are needed so that dental monitoring during pregnancy can meet the needs of pregnant women.